Historical determinants of neurosurgical inequities in Africa and the African diaspora: A review and analysis of coloniality - Ernest J. Barthélemy; Sylviane A. Diouf; Ana Cristina Veiga Silva; Nancy Abu-Bonsrah; Isabella Assunção Santos de Souza; Ulrick Sidney Kanmounye; Phabinly Gabriel; Kwadwo Sarpong; Edjah K. Nduom; Jean Wilguens Lartigue; Ignatius Esene; Claire Karekezi (Public Library of Science (PLoS), 2023)
The movement to decolonize global health challenges clinicians and researchers of sub-disciplines, like global neurosurgery, to redefine their field. As an era of racial reckoning recentres the colonial roots of modern health disparities, reviewing the historical determinants of these disparities can constructively inform decolonization. This article presents a review and analysis of the historical determinants of neurosurgical inequities as understood by a group of scholars who share Sub-Saharan African descent. Vignettes profiling the colonial histories of Cape Verde, Rwanda, Cameroon, Ghana, Brazil, and Haiti illustrate the role of the colonial legacy in the currently unmet need for neurosurgical care in each of these nations. Following this review, a bibliographic lexical analysis of relevant terms then introduces a discussion of converging historical themes, and practical suggestions for transforming global neurosurgery through the decolonial humanism promulgated by anti-racist practices and the dialogic frameworks of conscientization.